Electronic Student Worksheet Design (ELKPD) Mathematics to Improve Students' Numeracy Literacy and Social Interaction Skills - Haura Amara Rais; Nafida Hetty Marhaeni (Jurnal Mercumatika : Jurnal Penelitian Matematika dan Pendidikan Matematika, 2026)
Students' numeracy literacy and social interaction are important aspects of mathematics learning. Numeracy literacy in mathematics learning is influenced by the learning media used by students. Low social interaction will make students unenthusiastic about learning mathematics, which can result in low learning outcomes. Therefore, the purpose of this study was to analyze the need for mathematics learning media to improve students' numeracy literacy and social interaction. The research used was descriptive quantitative research. The subjects of the study were students of class VII A of SMP Negeri 2 Godean . The data collection techniques used were interviews, observations, and questionnaires. The results showed that 82% of students' numeracy literacy was moderate to low. In addition, 90% of the use of books and conventional methods was the main factor in low numeracy literacy and social interaction of students. The need for mathematics learning media is important because 72% of students agree with the use of mathematics learning media. Therefore, the development of mathematics learning media is needed to improve students' numeracy literacy and social interaction skills.